Pengaruh Kualitas Layanan Website Dan Kualitas Jasa Logistik Terhadap Keputusan Pembelian Ulang - Ageng Ginanjar Saputra; Sujana Sujana (Jurnal Informatika Kesatuan, 2021)
This research aims (1) to know how much influence the dimension of quality of use to website quality on the website blibli.com. (2) To find out how big the quality dimension of information on website quality is influenced on the website blibli.com. (3) To find out how much interaction service dimensions affect website quality on the website blibli.com. (4) To find out how much the website's quality affects the repurchase decision on the website blibli.com. (5) To know how much quality of logistic service is affected on the repurchase decision on the website blibli.com. (6) to find out how influential the quality of the use dimension is to repurchase decisions through website quality on the website blibli.com. (7) To find out how large the dimension of quality information is influenced by the website's quality of re-purchase decisions on the website blibli.com. (8) To find out how much interaction service dimensions affect the re-purchase decision through the quality of the website on the website blibli.com. This research uses variable independent (quality of use, quality of information, interaction services, Website quality and quality of logistics suits), variable dependent (Website quality and repurchase decision) variable intervening (Website quality). The number of respondents in this study amounted to 400 respondents which were taken from the average of transactions occurring monthly in the warehouse of Blibli.com in Bogor Regency. The research Data is processed using SPSS and Lisrel 8.80 tools. The results of the research (1) Quality of use have a positive and significant effect on Website quality based on the T value value of 3.12. (2) Quality of information provides a positive and significant effect on the quality of the Website based on the T value value of 4.44. (3) The interaction service provides a positive and significant effect on the quality of the Website based on the T value value of 30.46. In models 1.2 and the remaining 3 0.01 are influenced by factors that are not researched. (4) The quality of the Website provides a positive and significant effect on the repurchase decision based on the T value value of 5.50. (5) The quality of logistic services provides a positive and significant effect on the repurchase decision based on the T Value value of 2.01. On models 4 and 5 The remaining 0.19 are influenced by a factor that is not in meticulous. (6) The quality of use provides a positive and significant effect on the re-purchase decision through the quality of the website based on the T-value of the Sobel test of 4.2. (7) Quality of information provides a positive and significant effect on the repurchase decision through Website quality. Based on the T-value of the Sobel test of 4.8. (8) The interaction service provides a positive and significant effect on the repurchase decision through the Website quality with the based on T value of the Sobel test of 10.2. On models 7, 8 and 9 the remaining 0.20 are influenced from the factors that were not researched. Keywords: quality of Website services, quality of logistics services and repurchase decisions.